Evaluating the Use of Monetary Incentive in Text-Delivered Sexually Transmitted Infection Education - Townsend, Haley Franklin; Johnson, Paige (Building Healthy Academic Communities Journal, 2020)
Background: The Centers for Disease Control and Prevention (CDC) reported increases in chlamydia, gonorrhea, and syphilis from 2016 to 2017 despite numerous testing and education programs. In addition, young adults are at an increased risk of STIs. Aim: To describe the effectiveness of monetary incentives provided to college females for engaging with automated mobile messaging delivered education over the course of six weeks concerning sexually transmitted infections (STIs). Methods: A longitudinal cohort study was conducted at a large Southeastern, public university in the United States. One hundred and fifty-six female college students (18-24 years in age) participated in a mobile messaging and marketing automation platform delivered once a week for six weeks. Engagement with weekly education was measured by clicks on educational content. Results: Out of the six messages, χ2 analysis revealed that paid participants were more likely to engage with the STI education in weeks two, four, five, and six. In this study, simple linear regression ANOVA confirmed that compensation was the main extrinsic motivator for engagement rather than other factors, such as the delivery method. Conclusions: Monetary incentive can increase engagement with STI education in college females while mobile messaging also has the potential.